Angio in STEMI, Evaluating Pre-dilatation & Thrombus aspiration_Protocol & Flowdiagram - Rekha V (19645294) (2024)
This contains the study protocol and flow diagram of the article titled "Angiographic Outcomes in STEMI Patients: Evaluating Pre-dilatation and Thrombus Aspiration Effects"